Impact of Diabetes Mellitus on the Outcome of Pancreatic Cancer - Beg, Muhammad Shaalan (Public Library of Science, 2014)
INTRODUCTION: Diabetes mellitus (DM) has the potential to impact the pathogenesis, treatment, and outcome of pancreatic cancer. This study evaluates the impact of DM on pancreatic cancer survival. METHODS: We conducted a retrospective cohort study from the Veterans Affairs (VA) Central Cancer Registry (VACCR) for pancreatic cancer cases between 1995 and 2008. DM and no-DM cases were identified from comorbidity data. Univariate and multivariable analysis was performed. Multiple imputation method was employed to account for missing variables. RESULTS: Of 8,466 cases of pancreatic cancer DM status was known in 4728 cases that comprised this analysis. Males accounted for 97.7% cases, and 78% were white. Overall survival was 4.2 months in DM group and 3.6 months in the no-DM group. In multivariable analysis, DM had a HR = 0.91 (0.849–0.974). This finding persisted after accounting for missing variables using multiple imputations method with the HR in DM group of 0.93 (0.867–0.997). CONCLUSIONS: Our data suggest DM is associated with a reduction in risk of death in pancreatic cancer. Future studies should be directed towards examining this association, specifically impact of DM medications on cancer outcome.